Non-pecuniary Value of Employment and Natural Resource Extinction - Y. Hossein Farzin; Ken-Ichi Akao (Fondazione Eni Enrico Mattei (FEEM), 2006)
We assume that people value employment not only to earn income to satisfy their consumption needs but also as a means of community/social involvement that provides socio-psychological (non-pecuniary) benefits. We show that the latter incentive can encourage full employment harvesting resources and explain why poor resource-based communities may exhaust a natural resource in a finite time even if there is a sustainable path of resource consumption available. We show that communities could sustain their natural resources by using outside-the-community employment and economic diversification, but, to be effective, such policies must ensure that the outside wage rate and the initial capital stock are above certain minimum levels, which will be higher the longer these policies are delayed.
Keywords: E24; O12; O13; Q28; 330; Non-pecuniary effects; Employment value; Resource extinction; Sustainability; Beschäftigung; Natürliche Ressourcen; Nachhaltige Entwicklung; Theorie